Targeting Low-Phytate Soybean Genotypes Without Compromising Desirable Phosphorus-Acquisition Traits - Kuerban, Mireadili; Jiao, Wenfeng; Pang, Jiayin; Jing, Jingying; Qiu, Li-Juan; Ding, Wenli; Cong, Wen-Feng; Zhang, Fusuo; Lambers, Hans (Frontiers in Genetics, 2020)
Phytate-phosphorus (P) in food and feed is not efficiently utilized by humans and non-ruminant livestock, potentially contributing to high losses of P to the environment. Crops with high P-acquisition efficiency can access soil P effectively. It remains elusive whether crop genotypes with high P-acquisition efficiency can also have low seed phytate concentrations. A core collection of 256 soybean (Glycine max (L.) Merr.) genotypes from China with diverse genetic background were grown in the same environment and seeds were sampled to screen for seed phytate-P concentration. Some of these genotypes were also grown in a low-P soil in the glasshouse to measure root morphological and physiological traits related to P acquisition. Large genotypic variation was found in seed phytate-P concentration (0.69-5.49 mg P g-1 dry weight), total root length, root surface area, rhizosheath carboxylates, and acid phosphatase activity in rhizosheath soil. Geographically, seed phytate-P concentration was the highest for the genotypes from Hainan province, whereas it was the lowest for the genotypes from Inner Mongolia. Seed phytate-P concentration showed no correlation with any desirable root traits associated with enhanced P acquisition. Three genotypes (Shandonggaozuoxuan no1, Silihuang and Diliuhuangdou-2) with both low phytate concentrations and highly desirable P-acquisition traits were identified. This is the first study to show that some soybean genotypes have extremely low seed phytate concentrations, combined with important root traits for efficient P acquisition, offering material for breeding genotypes with low seed phytate-P concentrations.